The Family Contribution to Achieving the Dimension of Intellectual Security among Children: An Applied Study on Al-Bayda Governorate (The International Journal of Educational Sciences and Arts, 2024)
The current study aimed to identify the degree to which the family contributes to achieving the aspect of intellectual security among the children in Al-Bayda Governorate. To achieve the objectives of the study, the researcher used descriptive and analytical methods. The data collection tool was a questionnaire which was applied to the study sample consisting of (114) secondary school students (males and females.The study reached the following results:-  The contribution of family to the intellectual dimension was high with an average score of (3.75).-  The family contribution to the cultural dimension was high with an average score of (3.43).- The family contribution to the social dimension was also high with an average score of (3.85).The most prominent recommendations that emerged from this study were: - Benefiting from the list of intellectual dimensions and including them in the school curricula- Working to raise the cultural level of the family in line with the modern cognitive revolution and technological development.
Keywords: Contributions; Intellectual Security; Family